Importance of mastering communication skills of the english language in professional and job performance of the industrial managers of the Universidad Pedagógica y Tecnológica de Colombia - Ramos Bonilla, Sandra Lizeth (Universidad Pedagógica y Tecnológica de Colombia, 2018)
136 páginas : ilustraciones color, tablas, gráficas.